Evaluasi Wajib Pajak Terhadap Kemudahan Sistem Perpajakan Online - Nisrina, Ulfah Laila (Jurnal Ilmiah Manajemen & Kewirausahaan, 2025)
This study aims to evaluate taxpayers’ perceptions of the ease of use of the online tax system. Using a qualitative descriptive approach, the research explores how taxpayers experience and assess the usability of digital tax services in fulfilling their tax obligations. Data were collected through in-depth semi-structured interviews with purposively selected taxpayers who have used the online tax system, and the data were analyzed using qualitative thematic analysis. The findings indicate that the online tax system offers potential benefits in terms of accessibility and time efficiency. However, the perceived ease of use varies among taxpayers and is influenced by digital literacy, clarity of procedures, system reliability, and the availability of support services. Technical issues, complex processes, and limited guidance reduce users’ comfort and confidence in using the system. These findings suggest that the effectiveness of online tax systems should not be evaluated solely based on technological implementation, but also on users’ experiences and perceptions to ensure a more inclusive and user-oriented digital tax administration.